Великие философы: словарь-справочник / Л. В. Блинников - Блинников Леонтий Васильевич (Логос, 1998)
Экземпляры: РБ (20190212) / Инвентарный номер: 29506 / Цена: 22.00 / Авт.знак: Б 69 / ГРНТИ: 02 / ББК: 87.3я2